THE REVISED CHARTER AND ORDINANCES OF THE CITY OF DETROIT 199 (1855) § 10 - (:unkn) unknown (General Publisher, 1855)
Prohibited the discharge of any cannon. Violators fined twenty-five dollars.
--
Keywords: DISCHARGE